Collisions for the quantum Coulomb Hamiltonian - Gérard, Claude; Knauf, Andreas (Communications in Mathematical Physics, 1991)
We study the propagation of phase space singularities for the time dependent Schrödinger equation with potential having Coulomb-type singularities in space dimension equal tothree. We prove that the singularities (frequency set) of the solution are reflected by a Coulomb center exactly as in the classical problem, i.e. the frequency set follows theregularized trajectories of Classical Mechanics after a collision.